Регионална конференција: Ефектите на финасиската криза на Балканот и социјалдемократските одговори - Стамболиева, Марија (Ревија за социјална политика/Journal of Social Policy, 2009)
On October 16, 2009, a regional conference on the effects of the financial crisis in the Balkans and (socialdemocratic) responses was held in Skopje, organized by the Progress Institute for Social Democracy, the Friedrich Ebert Foundation and the European Forum for Democracy and Solidarity.